Investigation of schottky barriers at Pd-ZnO junctions in varistors. Issue 11 (September 2020) - Kaufmann, Benjamin; Raidl, Nadine; Supancic, Peter
Abstract: This is the first comprehensive study of the electrical behaviour, namely the I–V characteristics, of electrode-grain junctions in Pr-based ZnO varistor ceramics with Pd electrodes. These junctions have been investigated by a micro 4-point probe setup on the microstructural scale. A mean Schottky barrier height of 0.47 ± 0.03 eV was found. The reverse current through the junctions could be described by a model based on an interfacial layer. Furthermore, crystal orientations and polarities of grains with respect to the electrode layers were determined by electron back scatter diffraction and analysing etching patterns to check a possible influence on the barrier height. But within the set of experiments no correlation between grain orientation and barrier height could be found.